1 - Introduction: Agrarian Change, Food Security, Migration and Sustainable Development in Senegal and Zimbabwe - Dieng, Rama Salla; Banda, Geoffrey; Chambati, Walter (Africa Development, 2022)
African countries face multiple developmental, economic, social and industrial transformation hurdles, especially in the era of sustainable development and sensitivity to environmental damage. As late-comer industrialisers, there is some catching up to do, but they need to navigate complex, international, legal and institutional agreements that early industrialisers did not face. Given the environmental concerns, it is not surprising that the development thrusts encouraged are in agriculture and not in heavy industry. At the same time, many African countries are grappling food security, rural–urban and cross-border migration, and social, economic with industrial transformation challenges (Mkandawire 2001; Bruijn, Van Dijk and Foeken 2001; Diop 2008; Tsikata 2009; Patnaik, Moyo and Shivji 2011; Sall et al. 2011; Cheru and Modi 2013; Hall, Scoones and Tsikata 2015; Cross and Cliffe 2017; Bredeloup 2015; Jha, Chambati and Ossome 2021; Adesina 2021). This special issue brings together a broad range of papers exploring some of the myriad complexities faced by African countries. It focuses on Senegal and Zimbabwe, a western and a southern Africa country. The choice of countries was purposive as the editors had active networks in Zimbabwe and Senegal, and bringing together two...